2011
DOI: 10.1007/s00066-010-2184-4
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab as a Treatment Option for Radiation-Induced Cerebral Necrosis

Abstract: Radiation necrosis of normal CNS tissue represents one of the main risk factors of brain irradiation, occurring more frequently and earlier at higher total doses and higher doses per fraction. At present, it is believed that the necrosis results due to increasing capillary permeability caused by cytokine release leading to extracellular edema. This process is sustained by endothelial dysfunction, tissue hypoxia, and subsequent necrosis. Consequently, blocking the vascular endothelial growth factor (VEGF) at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Similar favorable results of fractionated stereotactic re-irradiation are documented in the literature [3,4,8,29]. More recent studies reported the integration of modern targeted chemotherapy into stereotactic re-irradiation and preliminary results are encouraging [10,17,25].…”
Section: Discussionsupporting
confidence: 68%
“…Similar favorable results of fractionated stereotactic re-irradiation are documented in the literature [3,4,8,29]. More recent studies reported the integration of modern targeted chemotherapy into stereotactic re-irradiation and preliminary results are encouraging [10,17,25].…”
Section: Discussionsupporting
confidence: 68%
“…Recently, bevacizumab, an anti-VEGF antibody was found to be effective in treatment of radiation-induced cerebral necrosis leading to radiographic response and to an improvement of cerebral edema with reduction of steroid medication. In experimental models, blockage of the VEGF-related pathway was also shown to reduce radiation-induced fibrosis in rectal tissues [31,33,34,44].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is the mainstay of therapy for NPC and greatly improves patient survival [2]. Along with promising therapeutic effects, complications such as radiation dermatitis [3], temporal lobe necrosis, cognitive impairment, and cranial nerve injury are also associated with radiotherapy [4,5,6]. Reports in the literature have described that cranial nerves were relatively radioresistant, and palsy was a rare complication after radiotherapy [7,8,9].…”
mentioning
confidence: 99%